Marketing Strategy for Hajj Program Financing (PROHAJJ) with Wakalah Bil Ujrah Wal Qard Akad at PT. Bank Muamalat Indonesia, Tbk Rantauprapat Branch - Siddik Bonar Pane; Mustapa Kamal Rokan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to provide information about the existence of a product financing the Hajj program with the Wakalah Bil Ujrah Wal Qard contract at PT. Bank Muamalat Indonesia, Tbk Rantauprapat Branch. The role of Islamic banking is to provide services that make it easier for Muslims to perform the pilgrimage. The majority of Indonesian people are Muslims, this is a very big opportunity that Islamic banks should take advantage of. We need the right marketing strategy in providing good and responsible service.